Workflow determinants of recovery efficiency in wastewater-based surveillance of respiratory viruses - M. Mozammel Hoque; Guangming Jiang; Ryo Honda; Harimurti Nuradji; David Muscatello; Martina Sanderson-Smith (Water Research, 2027)

Characterizing ionospheric perturbations with refined gradient ionosphere indices - Norbert Jakowski; M. Mainul Hoque; Juan Andrés Cahuasquí; Grzegorz Nykiel (GPS Solutions, 2026)
Precision and safety-critical Global Navigation Satellite System (GNSS) applications require high-fidelity monitoring of space weather conditions, particularly ionospheric disturbances. These systems are highly sensitive to sharp spatial gradients and rapid Total Electron Content (TEC) variations. To support both operational and scientific needs, this study proposes and evaluates two variants of the Gradient Ionosphere indeX (GIX): GIXM and GIXV. Derived from absolute TEC measurements at pairs of ionospheric piercing points (IPPs), the GIX quantifies gradients by dividing the TEC difference by the distance between IPPs. The GIXM method calculates the scalar average of these gradients, while GIXV computes the resultant gradient vector over regional scales (typically ≥ 500 × 500 km 2 ) to capture both magnitude and direction. Comparative analysis reveals a strong correlation between GIXM and the operational geodetic I95 index, confirming GIXM’s utility for disturbance scaling and reliability assessment. Accurate estimation of the GIXV vector requires sufficient spatial coverage, typically involving 35–45 IPPs. Furthermore, analyzing GIX dynamics within the Magnetosphere-Ionosphere-Thermosphere (MIT) framework demonstrates potential for predictive modeling. By tracking the equatorward propagation of high-latitude gradient structures, this framework enables the forecasting of GIXM I95 levels, offering a robust tool for mitigating GNSS risks.

Pilot-scale demonstration and feasibility study of nutrient recovery from human urine in a membrane bioreactor under acidic pH and elevated MLSS conditions - Andrea Merenda; A.H. Shafaghat; Weonjung Sohn; Hsin-Chieh Lin; Mohammad Mahbub Kabir; M. Mozammel Hoque; Sherub Phuntsho; Ho Kyong Shon (Journal of Water Process Engineering, 2026)

Computational identification of Azadirachta indica-derived inhibitors against VP39 methyltransferase of human monkeypox virus - Md. Shohel Hossain; Soharth Hasnat; Maria Mulla Mim; Md. Mehedi Hasan Pulok; MD. Faisal Patwary Hemal; Sangram Biswas; Bidduth Kumar Sarkar; Nilofa Yesmin; Raihana Sharmili; Mohammad Shah Alam; Tofazzal Islam; M. Nazmul Hoque (Next Research, 2026)

Low-dose inorganic arsenic exposure reprograms macrophages differentiation and function toward tumor-promoting phenotypes - Emily J. Illingworth; Sylvia S. Sanchez; Kristal A. Rychlik; Andre Kleensang; Jason Laird; Gabriel A. Lopez-Cecetaite; M. Carolina Rodriguez Steube; Aakriti Mathur; Pritam Sadhukhan; Daniel A. Medina-Cleghorn; Daniel Nomura; Martyn T. Smith; et al. (Environmental Research, 2026)

Invisible Dangers: A Risk Assessment of Cooking Biomass Fuels and Their Trace Element Exposure in Rural Bangladesh - Md. Badiuzzaman Khan; Muhammad Azizal Hoque; Mauro Masiol; Shamsunnahar Setu; Niger Sultana; M. Rafiqul Islam; Mahmud Hossain (Exposure and Health, 2026)

Trends in New York State light-duty vehicle fleet composition: Emission standards and engine technology (2013–2025) - Fariha Hoque Rimu; David Q. Rich; Gavin M. Lemley; Philip K. Hopke (Atmospheric Pollution Research, 2026)

Rooftop and surface garden soils in Bangladesh harbor diverse resistome profiles - M. Nazmul Hoque; Md. Liton Rana; Md Abu Ahsan Gilman; Pritom Kumar Pramanik; Md. Saiful Islam; Sadia Afrin Punom; Rabith Rahman; Jayedul Hassan; M. Shaminur Rahman; Srinivasan Ramasamy; Pepijn Schreinemachers; Ricardo Oliva; et al. (Environmental Monitoring and Assessment, 2026)

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Engineered exopolysaccharides from Weissella cibaria for texture enhancement and health benefits in fermented food matrices- a comprehensive review - Sumanth Suresh Patrimath; Omar Bashir; Imdadul Hoque Mondal; Prashant Anil Pawase; Muhammad Waseem; Aniket M. Pathare; Mudasir Ahmad (Food Research International, 2026)

Investigation and performance optimization of lead-free CsSn0.5Ge0.5I3 based perovskite solar cells - Dipayon Kumar Sikder; Sudip Paul; Swojan Datta Sammya; Sneha Deb; S. M. Tanbinul Hoque (Next Research, 2026)

Application of Botanical Extracts for Postharvest Preservation and Quality Enhancement of Horticultural Produce in Developing Countries: a Potential Review - Nayan Chandra Howlader; Md. Mokter Hossain; Tusar Kanti Roy; S. M. Ahsan; Md. Injamum-Ul-Hoque; Md. Hasan Miah (Journal of Crop Health, 2026)

Association between Arsenic Exposure and CCL5: its Implications in Asthma and Skin Lesions - Osman Goni; Nesar Uddin; Rajoana Karim Rimi; Kamrun Nahar Rossi; Faysal Abedin; Sharmin Akter Beauty; Sharon Jahan Sarder; Junayed Sadi; Mainul Islam; Victor Mondal; K M Ahsanul Kabir; Abu Eabrahim Siddique; et al. (Exposure and Health, 2026)

Health Risk Assessment of Women and Children Through Trace Elements from Biomass Cooking Fuels in Madhupur Tract Rural Community in Bangladesh - Muhammad Azizal Hoque; Niger Sultana; Sneha Gautam; Md. Al-Amin Khan; Md. Abdul Baten; M. Rafiqul Islam; Md. Badiuzzaman Khan (Aerosol Science and Engineering, 2026)

Assessing trace metal based human health risks in the highly consumed vegetables collected from the industrialized zones of Bangladesh - Ummeh Sadia; Md. Nazrul Islam; Md. Ashraful Hoque; Taznova Anwar Tanbi; S. M. Ashraful Abedin Asha; Sabbir Howlader; Nobonita Sarker; Shahidul Islam; Ismail Rahman; Amitava Bandyopadhyay; Sumon Ganguli (Environmental Geochemistry and Health, 2026)

Seasonal and Interannual Variability of Mixed-Layer Depth and Surface Chlorophyll-a in the Bay of Bengal: Insights into Physical-Biological Coupling - Siraj Uddin Md Babar Chowdhury; Md Minarul Hoque; Anik Karmakar; Nur Uddin Md Khaled Chowdhury; K. M. Azam Chowdhury; Tabassum Hossain Tahsin; Ashraful Moontahab (Ocean Science Journal, 2025)

First Molecular Characterization of Cryptosporidium and Giardia from Pigs in Bangladesh - Tania Sultana; Anas Bin Harun; Abdullah Al Bayazid; Md. Farhan Hasan; Ainun Nahar; Jinnat Rehena; Sourov Sutradhar; Joynti Saha; S. H. M. Faruk Siddiki; M. Nazmul Hoque; AMAM Zonaed Siddiki; Junqiang Li; et al. (Acta Parasitologica, 2025)

Relationship of fractalkine with arsenic exposure and the risk of cardiovascular diseases - Nesar Uddin; Rajoana Karim Rimi; Osman Goni; Nayan Chandra Mohanto; Kamrun Nahar Rossi; Faysal Abedin; Sharmin Akter Beauty; Biplob Ahmed; Sobuj Mia; Sharon Jahan Sarder; Sajib Hossain; Mainul Islam; et al. (Environmental Toxicology and Pharmacology, 2025)

First molecular detection and subtyping of Blastocystis in pigs raised by hilly ethnic communities in Bangladesh: a zoonotic concern - Jinnat Rehena; Anas Bin Harun; Abdullah Al Bayazid; Md. Farhan Hasan; Tania Sultana; Ainun Nahar; Joynti Saha; Mokammel Hossain Tito; Shuvo Singha; S. H. M. Faruk Siddiki; M. Nazmul Hoque; Md Robiul Karim (Veterinary Research Communications, 2025)

Genomic and In Vitro Analysis of Pediococcus pentosaceus MBBL4 Implicated Its Therapeutic Use Against Mastitis Pathogens and as a Potential Probiotic - Md. Morshedur Rahman; Naim Siddique; Md Abu Ahsan Gilman; Soharth Hasnat; Md. Golam Haider; Md. Morshedur Rahman; Anup Kumar Talukder; Abu Nasar Md. Aminoor Rahman; Tofazzal Islam; Ziban Chandra Das; M. Anwar Hossain; M. Nazmul Hoque (Probiotics and Antimicrobial Proteins, 2025)

Microplastic Ingestion, Polymer Characteristics, and Ecological Risk in Commercial Pomfret Fishes Pampus chinensis and Pampus argenteus from the Bay of Bengal - Md. Mostafa Monwar; Istiak Ahmed; Md Khurshid Alam Bhuiyan; Mohammad Rakibul Hoque; Anik Roy; Thoy Kamra Marma Joy; Shamima Afroj Mishu; Md. Mehedi Hasan Sagor; Niloy Barmon; Alam Pervez; Sarkar M. A. Kawsar (Bulletin of Environmental Contamination and Toxicology, 2025)

Genomic and Computational Analysis Unveils Bacteriocin Based Therapeutics against Clinical Mastitis Pathogens in Dairy Cows - Soharth Hasnat; Md. Morshedur Rahman; Farzana Yeasmin; Mohammad Jubair; Yosra A. Helmy; Tofazzal Islam; M. Nazmul Hoque (Probiotics and Antimicrobial Proteins, 2025)

Comprehensive immunoinformatics guided design and in silico assessment of a multi-epitope vaccine to elicit immunity against Mayaro virus - Md. Mashiur Rahaman; Mahmudul Hasan; G. M. Nurnabi Azad Jewel; Sumaiya Hasan; Shamsul H. Prodhan; Hammadul Hoque (In Silico Pharmacology, 2025)

Microplastic pollution scenario and its effects on public health and ecosystem: a Bangladesh perspective - A. N. M. S. Zawad; S. W. Rahman; A. Sultana; I. U. Chowdhury; M. R. Hoque (International Journal of Environmental Science and Technology, 2025)

Lomitapide: navigating cardiovascular challenges with innovative therapies - Undral Munkhsaikhan; Karima Ait-Aissa; Amal M. Sahyoun; Ehsanul Hoque Apu; Ammaar H. Abidi; Adam Kassan; Modar Kassan (Molecular Biology Reports, 2024)

Sensitivity analysis of cumulus parameterization scheme and data sources to simulate thunderstorms over Bangladesh using WRF model - M. Mozammel Hoque; Md. Salah Uddin Afsar; Mohammad Rashed Iqbal Faruque; S. Jamal Ahmed; A.T.M. Kaosar Jamil; M.A.K. Mallik; S.M. Quamrul Hassan (Advances in Space Research, 2024)

Recent advances on photocatalytic CO2 reduction using CeO2-based photocatalysts: A review - Khondaker Afrina Hoque; Sharmin Ara Sathi; Farjana Akter; Tania Akter; Tahsin Ahmed; Wahid Ullah; Kazi Arafin; Mohammad Sayadur Rahaman; Hossain M. Shahadat; Abu Bin Imran; Al-Nakib Chowdhury (Journal of Environmental Chemical Engineering, 2024)

Soil bacteriome diversity and composition of rooftop and surface gardens in urban and peri-urban areas of Bangladesh - Md. Liton Rana; M. Nazmul Hoque; M. Shaminur Rahman; Pritom Kumar Pramanik; Md. Saiful Islam; Sadia Afrin Punom; Srinivasan Ramasamy; Pepijn Schreinemachers; Ricardo Oliva; Md. Tanvir Rahman (Environmental Monitoring and Assessment, 2024)

The origin and water quality of spring systems in Monchique, Portugal: A focus on Long-Term sustainability and elevated sodium levels - M.A. Hoque; K.B. Amponsah; A. Blum; N. Walton; P. Dennis; A.P. Butler; S. Hugman; A. Bamberger; M. Fowler (Journal of Hydrology, 2024)

Correction to: Monitoring and prediction of land use land cover change of Chittagong Metropolitan City by CA-ANN model - I. Islam; K. F. Tonny; M. Z. Hoque; H. M. Abdullah; B. M. Khan; K. H. S. Islam; F. A. Prodhan; M. Ahmed; N. T. Mohana; J. Ferdush (International Journal of Environmental Science and Technology, 2024)

Influence of water chemistry and operating parameters on PFOS/PFOA removal using rGO-nZVI nanohybrid - Md. Arafat Ali; Utsav Thapa; Jonathan Antle; Ehsan Ul Hoque Tanim; John Michael Aguilar; Ian M. Bradley; Diana S. Aga; Nirupam Aich (Journal of Hazardous Materials, 2024)

Monitoring and prediction of land use land cover change of Chittagong Metropolitan City by CA-ANN model - I. Islam; K. F. Tonny; M. Z. Hoque; H. M. Abdullah; B. M. Khan; K. H. S. Islam; F. A. Prodhan; M. Ahmed; N. T. Mohana; J. Ferdush (International Journal of Environmental Science and Technology, 2024)

Seasonal morphology and solar activity dependence analysis of mid-latitude post-midnight enhancement using Global Ionospheric Map - Eman M. El-Desoky; Mohammed Mainul Hoque; M. Youssef; Ayman Mahrous (Advances in Space Research, 2024)

Correction: Impacts, challenges, and adaptation of small-scale fishers during the COVID-19 pandemic in selected tropical countries - Edison D. Macusi; Michael Jeriel I. Bersaldo; Robert E. Katikiro; Nur Fadli; K. H. M. Ashoka Deepananda; Mohammad Mojibul Hoque Mozumder (Aquatic Sciences, 2024)

Impacts, challenges, and adaptation of small-scale fishers during the COVID-19 pandemic in selected tropical countries - Edison D. Macusi; Michael Jeriel I. Bersaldo; Robert E. Katikiro; Nur Fadli; K. H. M. Ashoka Deepananda; Mohammad Mojibul Hoque Mozumder (Aquatic Sciences, 2024)

Maternal health outcomes associated with ambient air pollution: An umbrella review of systematic reviews and meta-analyses - Hoimonty Mazumder; Fariha Hoque Rimu; Monir Hossain Shimul; Jyoti Das; Easter Protiva Gain; Winston Liaw; M. Mahbub Hossain (Science of The Total Environment, 2024)

Uncovering the impact of mega-scale shipbreaking yards on soil and crop quality in Bangladesh: A spatiotemporal dynamics and associated health risks of metal/loid contamination - Md. Nazrul Islam; Sumon Ganguli; Narottam Saha; M. Mamun Huda; Md. Ashraful Hoque; Cheng Peng; Jack C. Ng (Journal of Hazardous Materials, 2024)

Characterization of lignin and hemicellulose degrading bacteria isolated from cow rumen and forest soil: Unveiling a novel enzymatic model for rice straw deconstruction - Bishal Sharker; Md. Aminul Islam; Md. Al Amin Hossain; Iqrar Ahmad; Abdullah Al Mamun; Sibdas Ghosh; Aminur Rahman; Md. Shohorab Hossain; Md. Ashikujjaman Ashik; Md. Rayhanul Hoque; Md. Khalid Hossain; M Al Mamun; et al. (Science of The Total Environment, 2023)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

Knowledge and practice of antimicrobial usage and resistance among poultry farmers: A systematic review, meta-analysis, and meta-regression - Abdullah Al Sattar; Nurun Nahar Chisty; Nusrat Irin; Md. Helal Uddin; F M Yasir Hasib; Md. Ahasanul Hoque (Veterinary Research Communications, 2023)

Ionosphere variability II: Advances in theory and modeling - Ioanna Tsagouri; David R. Themens; Anna Belehaki; Ja-Soon Shim; Mainul M. Hoque; Grzegorz Nykiel; Claudia Borries; Anna Morozova; Teresa Barata; Wojciech J. Miloch (Advances in Space Research, 2023)

Ionosphere variability I: Advances in observational, monitoring and detection capabilities - Ioanna Tsagouri; Anna Belehaki; David R. Themens; Norbert Jakowski; Tim Fuller-Rowell; Mainul M. Hoque; Grzegorz Nykiel; Wojciech J. Miloch; Claudia Borries; Anna Morozova; Teresa Barata; William Engelke; et al. (Advances in Space Research, 2023)

Polycyclic aromatic hydrocarbons in groundwater of oil-rich regions of upper Brahmaputra Valley, India: linkages of colloidal transport - Jinu Deka; Kali Prasad Sarma; Nitu Gupta; Md. Sahbaz Ahmed; M. A. Jafar Mazumder; Raza R. Hoque (Arabian Journal of Geosciences, 2023)

Ecofriendly pretreatment of cotton fabrics by ultrasonication and reusing bath chemicals - Mohammad M. U. Hoque; Sunzida H. Rimu; Abul K. Mallik; Mohammed Mizanur Rahman (Environmental Science and Pollution Research, 2022)

Performance of F1 progenies developed through crosses between Brassica carinata A. Braun A(♀) and Brassica rapa L (♂) - Barna Goswami; Nasima Momtaz; M. I. Hoque; R. H. Sarker (Genetic Resources and Crop Evolution, 2022)

Application of the novel state-of-the-art soft computing techniques for groundwater potential assessment - Alireza Arabameri; M. Santosh; Hossein Moayedi; John P. Tiefenbacher; Subodh Chandra Pal; Omid Asadi Nalivan; Romulus Costache; Naser Ahmed; Muhammad Al-Amin Hoque; Rabin Chakrabortty; Artemi Cerda (Arabian Journal of Geosciences, 2022)

Multilocus sequence typing of multidrug-resistant Salmonella strains circulating in poultry farms of Bangladesh - Khandokar Fahmida Sultana; Otun Saha; M. Nazmul Hoque; Munawar Sultana; M. Anwar Hossain (Brazilian Journal of Microbiology, 2021)

Genome-wide genetic marker analysis and genotyping of Escherichia fergusonii strain OTSVEF-60 - Otun Saha; Nadira Naznin Rakhi; M. Nazmul Hoque; Munawar Sultana; M. Anwar Hossain (Brazilian Journal of Microbiology, 2021)

Assessment of biogas generation potential from slaughterhouse wastes in Dhaka city, Bangladesh - Sayedus Salehin; Syed Shaheer Uddin Ahmed; Md. Ehasanul Hoque; Md. Salauddin Mrigdad; S. M. Ashef Hussain; S. M. Tahsin Intisar (Waste Disposal & Sustainable Energy, 2021)

Motion-Mode Echocardiographic Measurement of Cardiac Dimensions in Goats and Sheep - Vineet Kumar; M. Hoque; A. C. Saxena (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Anatomical, physiological, and chemical alterations in lichen (Parmotrema tinctorum (Nyl.) Hale) transplants due to air pollution in two cities of Brahmaputra Valley, India - Rebecca Daimari; Pranamika Bhuyan; Sharfaa Hussain; Sanjeeva Nayaka; M. A. Jafar Mazumder; Raza R. Hoque (Environmental Monitoring and Assessment, 2021)

Nanoadsorbents for wastewater treatment: next generation biotechnological solution - M. E. Ali; M. E. Hoque; S. K. Safdar Hossain; M. C. Biswas (International Journal of Environmental Science and Technology, 2020)

Mud crab fishery in climate vulnerable coastal Bangladesh: an analysis towards sustainable development - M. Mojibar Rahman; Shahroz Mahean Haque; Shams M. Galib; M. Ashraful Islam; Md. Taskin Parvez; Md. Nazmul Hoque; M. Abdul Wahab; Hillary Egna; Christopher Brown (Aquaculture International, 2020)

Biomonitoring by epiphytic lichen species—Pyxine cocoes (Sw.) Nyl.: understanding characteristics of trace metal in ambient air of different landuses in mid-Brahmaputra Valley - Rebecca Daimari; Pranamika Bhuyan; Sharfaa Hussain; Sanjeeva Nayaka; M. A. Jafar Mazumder; Raza Rafiqul Hoque (Environmental Monitoring and Assessment, 2020)

Impact of Climate Change and Land Use on Groundwater Salinization in Southern Bangladesh—Implications for Other Asian Deltas - M. A. Islam; M. A. Hoque; K. M. Ahmed; A. P. Butler (Environmental Management, 2019)

Development of a cylindrical polar coordinates shallow water storm surge model for the coast of Bangladesh - G. C. Paul; M. M. Murshed; M. R. Haque; M. M. Rahman; A. Hoque (Journal of Coastal Conservation, 2017)

Ionospheric correction using NTCM driven by GPS Klobuchar coefficients for GNSS applications - M. M. Hoque; N. Jakowski; J. Berdermann (GPS Solutions, 2017)

Design, Development and Field Evaluation of Manual-Operated Applicators for Deep Placement of Fertilizer in Puddled Rice Fields - Md. Abdul Wohab; Yam Kanta Gaihre; A. T. M. Ziauddin; M. A. Hoque (Agricultural Research, 2017)

Selection of minimum indicators of hydrologic alteration of the Gorai river, Bangladesh using principal component analysis - Mirza A. T. M. Tanvir Rahman; Sanjida Hoque; A H M Saadat (Sustainable Water Resources Management, 2017)

Monitoring contaminants of emerging concern from tertiary wastewater treatment plants using passive sampling modelled with performance reference compounds - Tamanna Sultana; Craig Murray; M. Ehsanul Hoque; Chris D. Metcalfe (Environmental Monitoring and Assessment, 2017)

Drinking water vulnerability to climate change and alternatives for adaptation in coastal South and South East Asia - M. A. Hoque; P. F. D. Scheelbeek; P. Vineis; A. E. Khan; K. M. Ahmed; A. P. Butler (Climatic Change, 2016)

Serum androgens and prostate cancer risk: results from the placebo arm of the Prostate Cancer Prevention Trial - Jeannette M. Schenk; Cathee Till; Ann W. Hsing; Frank Z. Stanczyk; Zhihong Gong; Marian L. Neuhouser; Juergen K. Reichardt; Ashraful M. Hoque; William D. Figg; Phyllis J. Goodman; Catherine M. Tangen; Ian M. Thompson (Cancer Causes & Control, 2016)

An alternative ionospheric correction model for global navigation satellite systems - M. M. Hoque; N. Jakowski (Journal of Geodesy, 2015)

Prospective study of human herpesvirus type 8 serostatus and prostate cancer risk in the placebo arm of the Prostate Cancer Prevention Trial - Siobhan Sutcliffe; Cathee Till; Frank J. Jenkins; Charlotte A. Gaydos; Phyllis J. Goodman; Ashraful M. Hoque; Ann W. Hsing; Ian M. Thompson; William G. Nelson; Angelo M. De Marzo; Elizabeth A. Platz (Cancer Causes & Control, 2015)

Tracing recharge to aquifers beneath an Asian megacity with Cl/Br and stable isotopes: the example of Dhaka, Bangladesh - M. A. Hoque; J. M. McArthur; P. K. Sikdar; J. D. Ball; T. N. Molla (Hydrogeology Journal, 2014)

Sources of low-arsenic groundwater in the Bengal Basin: investigating the influence of the last glacial maximum palaeosol using a 115-km traverse across Bangladesh - M. A. Hoque; J. M. McArthur; P. K. Sikdar (Hydrogeology Journal, 2014)
Pollution of groundwater in the Bengal Basin (Bangladesh and West Bengal, India) by arsenic (As) puts at risk the health of more than 100 million consumers. Using 1,580 borehole lithological logs and published hydrochemistry on 2,387 wells, it was predicted that low-As (<10 μg/L) groundwater exists, in palaeo-interfluvial aquifers of brown sand capped by a protective palaeosol, beneath at least 45,000 km 2 of the Bengal Basin. The aquifers were predicted to be at a depth of as little as 25 m below ground level (mbgl), and typically no more than 50 mbgl. The predictions were confirmed along an east–west traverse 115 km in length (i.e. across half of Bangladesh) by drilling 28 new boreholes to 91-m depth to reveal subsurface sedimentology, and by mapping As distribution in groundwater. The aquifers identified occur at typically <40 mbgl and so are accessible with local drilling methods. A protective palaeosol that caps the palaeo-interfluvial aquifers prevents downward movement into them of As-polluted groundwater present in shallower palaeo-channel aquifers and ensures that the palaeo-interfluvial aquifers will yield low-As groundwater for the foreseeable future. Their use, in place of the shallower As-polluted palaeo-channel aquifers, would rapidly mitigate the health risks from consumption of As-polluted groundwater.

Consumption of unsafe food in the adjacent area of Hazaribag tannery campus and Buriganga River embankments of Bangladesh: heavy metal contamination - G. M. Rabiul Islam; Faysal Elahi Khan; Md. Mozammel Hoque; Yeasmin Nahar Jolly (Environmental Monitoring and Assessment, 2014)

Mitigating Global Warming Potentials of Methane and Nitrous Oxide Gases from Rice Paddies under different irrigation regimes - Muhammad Aslam Ali; M. Anamul Hoque; Pil Joo Kim (Ambio, 2013)

Nested numerical scheme in a polar coordinate shallow water model for the coast of Bangladesh - M. Mizanur Rahman; Gour Chandra Paul; Ashabul Hoque (Journal of Coastal Conservation, 2013)

Leaf phenological traits and leaf longevity of three mangrove species (Rhizophoraceae) on Okinawa Island, Japan - Sahadev Sharma; Md. Kamruzzaman; A. T. M. Rafiqul Hoque; Akio Hagihara (Journal of Oceanography, 2012)

Litterfall of three subtropical mangrove species in the family Rhizophoraceae - Md. Kamruzzaman; Sahadev Sharma; A. T. M. Rafiqul Hoque; Akio Hagihara (Journal of Oceanography, 2012)

Emergence of multidrug-resistant NDM-1-producing Gram-negative bacteria in Bangladesh - M. A. Islam; P. K. Talukdar; A. Hoque; M. Huq; A. Nabi; D. Ahmed; K. A. Talukder; M. A. C. Pietroni; J. P. Hays; A. Cravioto; H. P. Endtz (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

In vitro flowering and seed formation in lentil (Lens culinaris Medik.) - R. H. Sarker; Subroto K. Das; M. I. Hoque (In Vitro Cellular & Developmental Biology - Plant, 2012)

Prospective study of cytomegalovirus serostatus and prostate cancer risk in the Prostate Cancer Prevention Trial - Siobhan Sutcliffe; Cathee Till; Charlotte A. Gaydos; Frank J. Jenkins; Phyllis J. Goodman; Ashraful M. Hoque; Ann W. Hsing; Ian M. Thompson; Jonathan M. Zenilman; William G. Nelson; Angelo M. De Marzo; Elizabeth A. Platz (Cancer Causes & Control, 2012)

Open-Label Randomized Clinical Trial of Atropine Bolus Injection Versus Incremental Boluses Plus Infusion for Organophosphate Poisoning in Bangladesh - Mohammed Joynal Abedin; Abdullah Abu Sayeed; Ariful Basher; Richard J Maude; Gofranul Hoque; M. A. Faiz (Journal of Medical Toxicology, 2012)

A new global TEC model for estimating transionospheric radio wave propagation errors - N. Jakowski; M. M. Hoque; C. Mayer (Journal of Geodesy, 2011)

Serum estrogen levels and prostate cancer risk in the prostate cancer prevention trial: a nested case–control study - Song Yao; Cathee Till; Alan R. Kristal; Phyllis J. Goodman; Ann W. Hsing; Catherine M. Tangen; Elizabeth A. Platz; Frank Z. Stanczyk; Juergen K. V. Reichardt; Li Tang; Marian L. Neuhouser; Regina M. Santella; et al. (Cancer Causes & Control, 2011)

The endangered forests of Bangladesh: why the process of implementation of the Convention on Biological Diversity is not working - Sabir Bin Muzaffar; M. Anwarul Islam; Dihider Shahriar Kabir; Mamunul Hoque Khan; Farid Uddin Ahmed; Gawsia Wahidunnessa Chowdhury; M. Abdul Aziz; Suprio Chakma; Israt Jahan (Biodiversity and Conservation, 2011)

Factors limiting the health of semi-scavenging ducks in Bangladesh - M. A. Hoque; L. F. Skerratt; A. J. C. Cook; S. A. Khan; D. Grace; M. R. Alam; A. Vidal-Diez; N. C. Debnath (Tropical Animal Health and Production, 2011)

Monitoring the health and production of household Jinding ducks on Hatia Island of Bangladesh - M. A. Hoque; L. F. Skerratt; M. A. Rahman; M. A. Alim; D. Grace; B. Gummow; A. B. M. Rabiul Alam Beg; N. C. Debnath (Tropical Animal Health and Production, 2011)

Factors limiting traditional household duck production in Bangladesh - M. A. Hoque; L. F. Skerratt; M. A. Rahman; A. B. M. Rabiul Alam Beg; N. C. Debnath (Tropical Animal Health and Production, 2010)

Novel flavonoid glycosides from the bulbs of Urginea indica Kunth - Nasim Sultana; Kaisarun Akter; Nilufar Nahar; M. Shahinul Hoque Khan; M. Mosihuzzaman; Md Hossain Sohrab; Karsten Krohn (Natural Product Research, 2010)

Intra-individual variation in serum C-reactive protein over 4 years: an implication for epidemiologic studies - Elizabeth A. Platz; Siobhan Sutcliffe; Angelo M. De Marzo; Charles G. Drake; Nader Rifai; Ann W. Hsing; Ashraful Hoque; Marian L. Neuhouser; Phyllis J. Goodman; Alan R. Kristal (Cancer Causes & Control, 2010)

Detection of potato spindle tuber viroid (PSTVd) in minute amounts of potato (Solanum tuberosum L.) leaf tissue by hybridization techniques and, together with potato viruses, by multiplex RT-PCR - M. S. Khan; C. Timmermann; M. I. Hoque; R. H. Sarker; H.-P. Mühlbach (Journal of Plant Diseases and Protection, 2009)

Shifting regime shifted policy—interplay of interests in sustainability discourses of forest land use - Mohammad Ali; A. T. M. Rafiqul Hoque (Mitigation and Adaptation Strategies for Global Change, 2009)

Effect of pineapple disease on germination and yield contributing parameters of some promising varieties of sugarcane - F. Begum; M. I. Talukder; M. Z. Hoque (Sugar Tech, 2008)

Mitigation of higher order ionospheric effects on GNSS users in Europe - M. Mainul Hoque; N. Jakowski (GPS Solutions, 2008)

Declining groundwater level and aquifer dewatering in Dhaka metropolitan area, Bangladesh: causes and quantification - Mohammad A. Hoque; M. Mozzammel Hoque; Kazi Matin Ahmed (Hydrogeology Journal, 2007)

Pressure distribution phenomena over a wedge and sphere surface in uniform flow - M. Sohel Rana; A. T. M. Rafiqul Hoque; S. M. Asadul Hossain (International Journal of Environmental Science and Technology, 2007)

Higher order ionospheric effects in precise GNSS positioning - M. Mainul Hoque; N. Jakowski (Journal of Geodesy, 2007)

People’s attitude and use of forestland: Co-evolution of forest administration in Bangladesh - Mohammad Ali; M. Alamgir Kabir; A. T. M. Rafiqul Hoque (Small-scale Forestry, 2006)

Dissociation (Ds) constructs, mapped Ds launch pads and a transiently-expressed transposase system suitable for localized insertional mutagenesis in rice - Narayana M. Upadhyaya; Qian-Hao Zhu; Xue-Rong Zhou; Andrew L. Eamens; Mohammad S. Hoque; Kerrie Ramm; Ramannee Shivakkumar; Kathryn F. Smith; Shu-Ting Pan; Suzhi Li; Kefan Peng; Song J. Kim; et al. (Theoretical and Applied Genetics, 2006)

Albendazole Resistance in Gastrointestinal Nematode Parasites of Cattle in Bangladesh - M.N. Hoque; N. Begum; M. Nooruddin (Tropical Animal Health and Production, 2003)

Molecular epidemiologic studies within the Selenium and Vitamin E Cancer Prevention Trial (SELECT) - Ashraful Hoque; Demetrius Albanes; Scott M. Lippman; Margaret R. Spitz; Phillip R. Taylor; Eric A. Klein; Ian M. Thompson; Phyllis Goodman; Janet L. Stanford; John J. Crowley; Charles A. Coltman; Regina M. Santella (Cancer Causes & Control, 2001)

Efficient in vitro germination and shoot proliferation of chilling-treated water chestnut (Trapa japonica Flerov) embryonal explants - A. Hoque; S. M. Rahman; S. Arima; Y. Takagi (In Vitro Cellular & Developmental Biology - Plant, 2001)

Lunar spawning in Siganus canaliculatus - M. M. Hoque; A. Takemura; M. Matsuyama; S. Matsuura; K. Takano (Journal of Fish Biology, 1999)
A major spawning of the seagrass rabbitfish Siganus canaliculatus occurred 4 days after the new moon in both May and June 1993, and 7 days after the new moon in 1994. The gonadosomatic index ( I G ) and serum vitellogenin (VTG) levels fluctuated according to the lunar cycle; IG and VTG levels showed peaks at around the new moon and the waning moon, respectively, suggesting that spawning of this species is synchronized with the lunar cycle. Vitellogenic oocytes appeared on day 2 after the first spawning and were fully mature on day 30. When a greater percentage of the most advanced oocytes attained the tertiary yolk stage, they formed a batch and separated from the adjacent group of smaller pre‐vitellogenic oocytes, indicating that S. canaliculatus is a multiple spawner with an ovary belonging to the group‐synchronous type of oocyte development. Batch fecundity, assessed using batches of oocytes at and after the tertiary yolk stage, ranged from c. 0·52 to 2·56 million eggs. The relationship between batch fecundity (F) and fork length (1) can be represented as F=0·0536854L 5·07292.

Circulating levels and in vitro production of two maturation-inducing hormones in teleost: 17α,20β-dihydroxy-4-pregnen-3-one and 17α,20β,21-trihydroxy-4-pregnen-3-one, in a daily spawning wrasse, Pseudolabrus japonicus - M. Matsuyama; K. Ohta; S. Morita; M.M. Hoque; H. Kagawa; A. Kambegawa (Fish Physiology and Biochemistry, 1998)

Effect of hydrogen sulphide on liver somatic index and Fulton's condition factor in Mystus nemurus - M. T. Hoque; F. M. Yusoff; T. Law; M. A. Syed (Journal of Fish Biology, 1998)
The growth rate and liver somatic index were significantly ( P Mystus nemurus exposed to hydrogen sulphide compared to controls. These differences increased with corresponding increases in hydrogen sulphide concentrations. No significant differences ( P >0.05) in Fulton's condition factor were detected between the exposed fish and the controls. The results revealed that liver somatic index is a more sensitive indicator of hydrogen sulphide toxicity compared to Fulton's condition factor.